2005
DOI: 10.1536/ihj.46.639
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy Is Related to the Angiographically Detected Severity and Extent of Coronary Artery Disease in Patients With Type 2 Diabetes Mellitus

Abstract: SUMMARYDiabetic retinopathy (DR) is an early and frequent marker of other vascular complications of diabetes and its relation with coronary ischemia is known. The aim of the present study was to evaluate the association between DR and indices of coronary artery disease (CAD) severity and extent determined by coronary angiography.Sixty-nine diabetic patients undergoing coronary angiography for suspected CAD were evaluated. The severity and extent of CAD were scored from coronary angiograms by using 3 scores. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 15 publications
6
30
0
1
Order By: Relevance
“…Studies have shown that diabetic individuals with retinopathy are more likely to have myocardial perfusion defects (11,31,32), poorer coronary flow reserve (33), and lower coronary collateral score (34) than those without retinopathy. Moreover, diabetic retinopathy has also been associated with higher degrees of coronary calcification (35) and more diffuse and severe coronary artery stenosis on angiograms (36). These observations, in conjunction with ours, support the concept that micro-and macrovascular complications of diabetes share common pathogenic mechanisms (16,37) beyond those related to the risk factors adjusted for in our multivariate models.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that diabetic individuals with retinopathy are more likely to have myocardial perfusion defects (11,31,32), poorer coronary flow reserve (33), and lower coronary collateral score (34) than those without retinopathy. Moreover, diabetic retinopathy has also been associated with higher degrees of coronary calcification (35) and more diffuse and severe coronary artery stenosis on angiograms (36). These observations, in conjunction with ours, support the concept that micro-and macrovascular complications of diabetes share common pathogenic mechanisms (16,37) beyond those related to the risk factors adjusted for in our multivariate models.…”
Section: Discussionsupporting
confidence: 88%
“…The differences in results between studies may be attributable to the study methods. The association found between DR and CAS in this study is similar to the association discovered in the previous studies, 6,28 but not consistent with data from a recent study. 8 A previous study about association of DR with CAD demonstrated that the mean coronary artery calcium (CAC) score, a quantitative marker of CAS burden, measured by electron beam CT and multidetector CT, was significantly greater in T1DM patients with DR than in those without DR. 28 This study was only limited to T1DM and had no evaluation of noncalcified coronary plaques, an early and basic pathologic change of CAD, which have been suggested to be associated with CAS compared to calcified plaques when detected by multislice computed tomography (MSCT).…”
Section: Discussionsupporting
confidence: 64%
“…Of note, this association remained robust and significant using several different approaches to analyze CAC. Only one other study, comprised of a small group of patients preselected for suspected CVD, has explored the relationship between retinopathy and coronary atherosclerosis and demonstrated a relationship between retinopathy, assessed during opthalmoscopic fundus exams, and coronary angiogram severity (32).…”
Section: Statistical Analysesmentioning
confidence: 99%